Phytosfere '99 : highlights in European plant biotechnology research and technology transfer : proceedings of the Second European Conference on Plant Biotechnology, held in Rome, Italy, 7-9 June 1999 - European Conference on Plant Biotechnology 1999 : Rome, Italy); Vries, Gert E. de.; Metzlaff, Karin; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2000)
Humans face the challenge of producing enough food to meet the demands imposed by economic, biological and agricultural factors: rising population; rising income; and an expectation of higher quality food and a more diverse diet; decreasing amount of land available for food production; lowering environmental impact of agricultural practices and preserving biodiversity. Biotechnology is one of the most exciting and dynamic industries of our day. It offers us the possibility of reducing our dependence on intensive farming. Plant biotechnology is central to the search for effective, environmentally safe and economically sound alternatives to the use of chemical pesticides and the exhaustion of natural resources. Today, applied plant science has four overall goals: increased crop yield, improved crop quality, reducing production costs and reducing negative environmental impact. Biotechnology is proving its value in meeting these goals. It offers farmers higher yielding crops with lower costs of production and new outlets such as nutraceuticals and crop-based bio-factories. It offers the European economy the potential of high quality, knowledge based job creation and the European consumer better quality, tastier and more nutritious food. Though there is public concern of genetic engineering, those who are close to the science understand that this is the next big frontier to be crossed. The potential and opportunities offered by plant biotechnology must not be missed. We must go forward on that basis rather than turning our backs on the science. Phytosfere'99 provides a comprehensive overview for plant biotechnology. It combines specific scientific articles, review articles and comments from outside people on it, which is unique in European Literature.
Preface -- Introduction -- Opportunities and challenges of European plant biotechnology -- Control of genes -- Mapping gene location -- Controlling development and architecture -- Response to challenges of the environment -- Uncovering metabolic pathways -- Entrepreneurship in plant science -- Author index.
Includes bibliographical references.
Elsevier
Keywords: Plant biotechnology -- Congresses; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture; Plant biotechnology; Electronic books